Study on Aerodynamic Performance of a Straight-Bladed VAWT Using a Wind-Gathering Device With Polyline Hexagonal Pyramid Shape - Li, Yan; Tong, Guoqiang; Zhao, Bin; Feng, Fang; Tagawa, Kotaro (Frontiers in Energy Research, 2022)
The self-starting performance and aerodynamic characteristics at low wind speeds are the two main problems for the Straight-bladed Vertical Axis Wind Turbine (SB-VAWT). In this study, a new kind of Wind Gathering Device (WGD), which can be installed up and down the rotor, with a polyline hexagonal pyramid shape, was proposed. Both the numerical simulation and the wind tunnel test were performed on this WGD. Based on the method of quadratic rotary orthogonal combination design, the effect of the main structural parameters of the WGD on the self-starting performance of the SB-VAWT was researched by 3D numerical simulation. The optimal combination of the main structural parameters for the WGD under the condition of this study was obtained. Furthermore, wind tunnel tests were carried out on the SB-VAWT without and with the WGD having the optimal structural parameters, including the starting performance, power performance, and rotational revolutions performance. The results showed that both the static and dynamic performance of the SB-VAWT was increased to some degree by installing this kind of WGD. The improvement is more obvious under the condition of low wind speed. This research can be a useful reference for the in-depth study on the optimal WGDs for the SB-VAWTs.